Factors influencing food preferences and eating behaviour among the Forcibly Displaced Myanmar Nationals (FDMN) adolescents in Cox's Bazar, Bangladesh: a cross-sectional survey - Mahamudul Hasan; Azaz Bin Sharif; Rashedul Islam; A B M Nahid Hasan; Nusrat Jahan Ferdous (BMJ Publishing Group, 2024)
Background Adolescence is a pivotal period for physical, mental, social and behavioural development, so it is crucial to understand the factors influencing adolescent food preferences and eating behaviour. This study aimed to investigate the factors that influence adolescents' food preferences and eating behaviours in the Forcibly Displaced Myanmar Nationals (FDMN) camp in Cox's Bazar, Bangladesh.Methods A cross-sectional study was conducted in the FDMN camp, recruiting 545 adolescents. The purposive sampling technique was applied. First, 12 camps in the Ukhiya region were randomly selected. Adolescents of both sexes, aged between 10 and 19, were included in the study. Respondents' sociodemographic characteristics and dietary patterns, as well as the participant's nutritional status, were recorded. Descriptive statistics were used to present the baseline characteristics, while Pearson's χ2 test was used to assess the relationship between food preference and baseline characteristics.Results A significant number of participants failed to meet their daily requirements for essential nutrients, including protein (89.9%), vegetables (82.8%) and dairy products (90.8%). Additionally, 58.9% of the respondents did not consume adequate water daily. Food preferences and eating behaviours among FDMN adolescents in Cox's Bazar were found to be influenced by a range of factors, including peer influence, access to nutritional education, food sources, cultural beliefs, ration sufficiency, food prices as well as age, gender, education level and household income.Conclusions In conclusion, understanding and addressing the multifaceted factors that influence the food preferences of FDMN adolescents is crucial for developing targeted interventions and comprehensive nutritional programmes.